The cardiovascular system in patients with anthracycline cardiomiopathy - Alexandr T. Teplyakov; Sergey N. Shilov; Anna A. Popova; Elena V. Grakova; Ekaterina N. Berezikova; Maria N. Neupokoeva; Alexey V. Molokov; Kristina V. Kopeva; Vadim V. Kalyuzhin (Бюллетень сибирской медицины)
Aim. The purpose of this study was to examine the incidence of early and late cardiotoxicity in women receiving anthracycline antibiotics during breast cancer chemotherapy treatment as well as possible links of anthracycline-induced cardiomyopathy with endothelial dysfunction and inflammation.Materials and methods. A 12-month cohort study included 148 women with breast cancer who received anthracycline antibiotics as a part of chemotherapy regimens. Echocardiography and ultrasound examination of the brachial artery were performed in all patients before chemotherapy, after the first round of therapy, and one year after inclusion in the study. Patients were divided into two groups based on the results of a preliminary examination. Group 1 consisted of 34 patients who had developed dysfunction from the 1st type associated with antitumor chemotherapy, and group 2 was comprised of 114 patients with preserved LVEF.Serum concentrations of tumor necrosis factor-α (TNF-α) and interleukin-1β (IL-1β) were determined after the end of antineoplastic chemotherapy by ELISA.Results. After one year of combined treatment with anthracyclines, 23% of breast cancer patients had a depression of global systolic function in the left ventricle (reduction of the ejection fraction by 10% or more from baseline), which was associated with a change in geometry (an increase in the cavity and a decrease in the relative thickness of the walls). On the one hand, the changes in the structural and functional parameters of the left ventricle were connected with the total dose of doxorubicin and associated with a decrease in the growth of the brachial artery diameter in the reactive hyperemia test. On the other hand, the changes were associated with an increase in serum concentration of proinflammatory cytokines TNF-α and IL-1β).Conclusions. The incidence of late dysfunction of the first type associated with antitumor chemotherapy for breast cancer is 23%. Cardiovascular injuries caused by chemotherapy with anthracyclines are dose-dependent and are accompanied by the development of vasomotor dysfunction of the endothelium of the brachial artery. Excess anti-inflammatory cytokines (TNF-α and IL-1β) in the sera of patients who developed a depression of global left ventricular systolic function in a separated period of antitumor chemotherapy seems to reflect the role of systemic inflammation in the mechanisms of anthracycline-induced cardiomyopathy development.